2000
DOI: 10.1101/gad.843200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the three Rb-related genes leads to loss of G1 control and immortalization

Abstract: The retinoblastoma protein, pRB, and the closely related proteins p107 and p130 are important regulators of the mammalian cell cycle. Biochemical and genetic studies have demonstrated overlapping as well as distinct functions for the three proteins in cell cycle control and mouse development. However, the role of the pRB family as a whole in the regulation of cell proliferation, cell death, or cell differentiation is not known. We generated embryonic stem (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
519
6
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(566 citation statements)
references
References 58 publications
30
519
6
9
Order By: Relevance
“…The IC 50 of doxorubicin against U-2 OS RB(À) cells was about four fold higher than that against U-2 OS RB( þ ) cells (data not shown). Previous studies using MEFs derived from triple knockout of the RB family (TKO MEF), and NIH3T3 cells expressing HPV E7 protein, suggest that all members of the RB family are involved in DNA damage-induced checkpoint (Sage et al, 2000;Polager and Ginsberg, 2003). Our data indicate that RB loss alone is sufficient to abrogate the G2/M checkpoint in human cells independently of p107 and p130.…”
Section: Establishment Of Stable Rb Knockdown Cell Linessupporting
confidence: 49%
See 1 more Smart Citation
“…The IC 50 of doxorubicin against U-2 OS RB(À) cells was about four fold higher than that against U-2 OS RB( þ ) cells (data not shown). Previous studies using MEFs derived from triple knockout of the RB family (TKO MEF), and NIH3T3 cells expressing HPV E7 protein, suggest that all members of the RB family are involved in DNA damage-induced checkpoint (Sage et al, 2000;Polager and Ginsberg, 2003). Our data indicate that RB loss alone is sufficient to abrogate the G2/M checkpoint in human cells independently of p107 and p130.…”
Section: Establishment Of Stable Rb Knockdown Cell Linessupporting
confidence: 49%
“…In the RKO cells expressing E7, both the amount and activity of G2-M regulatory CDKs (cyclin B1/CDK1 and CDK2) were highly elevated compared to the parental cells with functional RB family proteins, which resulted in the escape from G2/M cell cycle arrest caused by doxorubicin treatment. In addition, TKO MEF cells, but not RBÀ/À MEF cells, canceled the DNA damageinduced G1/S checkpoint, indicating that all the three pocket proteins, RB, p107 and p130, appeared to be cooperatively involved in this mechanism (Sage et al, 2000). Interestingly, the present results showed that RB inactivation alone in U-2 OS cells without any alteration of p107 and p130 could over-ride the G2/M DNA damage checkpoint induced by doxorubicin.…”
Section: Green) U-2 Os Rb( þ ) Cells Treated With Doxorubicin (A-c)mentioning
confidence: 45%
“…Although Rb À cells lack any restriction point for protein synthesis inhibition, their proliferation can be stopped by GF deprivation (Herrera et al, 1996), suggesting that GFs have other effects on the cell-cycle engine, mediated presumably by Rb-related proteins, p130 and p107. If all three ''pocket proteins'' (Rb, p130 and p107) are deleted, then cells undergo significant proliferation in the absence of GFs (Sage et al, 2000).…”
Section: Zetterberg-larsson Experimentsmentioning
confidence: 99%
“…Although MEFs deficient in any one of the inhibitory E2Fs or in both p107 and p130 proliferate normally, they show defects in response to growth inhibitory signals. Triple knockout MEFs deficient in all three pocket proteins show increased entry into S phase, loss of contact inhibition, and resistance to senescence and DNA-damage-induced G1 arrest (Dannenberg et al, 2000;Sage et al, 2000).…”
Section: Cell Cycle Roles Of the Rb Family Of Proteinsmentioning
confidence: 99%